Rechargeable Al-metal aqueous battery using NaMnHCF as cathode : investigating the role of coated-Al anode treatments for supe-rior battery cycling performance - Kumar, Sonal (2021)
Rechargeable Al-ion aqueous batteries (AIABs) are emerging contenders for massive battery systems due to economic, abundance, environmental, and safety advantages. However, the high capacity of metallic-Al remains untapped due to native oxide barrier formation. Engineering oxide removal by treating Al metal with an ionic liquid mixture solves this problem but the role of this treated-Al (TAl) in influencing full-cell battery performance is not yet fully understood. At the same time, the stability and compatibility of the coating layer applied on Al metal remain unexplored for long-term handling in full-cell assembly lines. Here, we explore the above two aspects of TAl in the context of a full-cell AIAB. First, a highly stable cathode material, NMnHCF, is demonstrated to successfully store an Al-ion by reversibly transforming from the monoclinic to tetragonal phase. A high energy density surpassing previous equivalent reports has been reported. Second, it is revealed that combinations of electrolyte–TAl pairings significantly influence the overall battery performance, wherein electrolyte conductivity influences the Al plating/stripping overpotential, which in turn dictates the overall battery performance. We also document that chlorinated coatings on TAl are stable under ambient atmosphere for at least 40 h and prevent reoxidation of the bulk aluminum metal during battery fabrication and electrochemical cycling